Recent Advances in Aluminum Phytotoxicity - (:unkn) unknown (Springer Science and Business Media B.V., 2020)
Aluminum (Al) is the third most abundant metal in the earth’s crust after oxygen and silicone. Geologically Al has existed as a complex compound with oxygen and carbon. In addition to natural Al in the soil, in the last century Al is used in various types of industrial products giving rise to excessive accumulation in the soil. When soil pH decreases under 5, complex Al dissolves into phytotoxic forms. Al3+, which is the most phytotoxic form, is absorbed by plant roots and has adverse effects on plant growth and development. Al toxicity is an important agricultural problem causing dramatic yield decrease and has been substantially investigated in plant systems. The mechanisms of Al toxicity and tolerance in plants have been described as morphological, physiological, and molecular perspectives; however, it has not yet been fully elucidated because of its complex chemistry. It has been considered that metal toxicity has been controlled genetically. To study the molecular genetics of Al toxicity and tolerance are important issues in the field of plant growth and development. The development and application of Al-tolerant cultivars in fields is a better environmental solution to permit agricultural production in regions with acidic soils. Thus to clarify the signaling pathways and molecular markers for the fast and accurate diagnosis of Al toxicity symptoms may help to create strategies for strengthening Al tolerance in plants. This review summarizes the responses to Al and proposed molecular mechanisms of Al toxicity and tolerance in plants. © Springer Nature Switzerland AG 2020.
Keywords: Al tolerance; Al toxicity; Oxidative stress; Programmed cell death